2004
DOI: 10.1111/j.1472-765x.2004.01599.x
|View full text |Cite
|
Sign up to set email alerts
|

A heat inducible tyrosinase with distinct properties from Bacillus thuringiensis

Abstract: Aims: The objective of this work was to purify the tyrosinase from Bacillus thuringiensis subsp. kurstaki (Bt) (CCTCC AB 90010) and study its enzymatic properties. Methods and Results: A 'one-step' purification method was used in this work, which was an easy, high-yield purification method. Tyrosinase activity of this purity was measured under different conditions to study its kinetic characterizations. The optimum pH and thermal stability of this enzyme were also determined. The results revealed that the tyro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
33
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 14 publications
3
33
0
Order By: Relevance
“…The identity of the bacteria was also confirmed by biochemical assays. To date, there are several reports on tyrosinase from B. thuringiensis strains [Dalfard et al, 2006;Liu et al, 2004;Ruan et al, 2005], and there is a putative tyrosinase gene located on a 208-kb plasmid of B. cereus 10987 [Rasko et al, 2004]. There is no description of a tyrosinase from B. megaterium , making tyrosinase-VS1 a novel enzyme.…”
Section: Isolation and Identification Of A Tyrosinaseexpressing Bactementioning
confidence: 99%
See 2 more Smart Citations
“…The identity of the bacteria was also confirmed by biochemical assays. To date, there are several reports on tyrosinase from B. thuringiensis strains [Dalfard et al, 2006;Liu et al, 2004;Ruan et al, 2005], and there is a putative tyrosinase gene located on a 208-kb plasmid of B. cereus 10987 [Rasko et al, 2004]. There is no description of a tyrosinase from B. megaterium , making tyrosinase-VS1 a novel enzyme.…”
Section: Isolation and Identification Of A Tyrosinaseexpressing Bactementioning
confidence: 99%
“…The latter value suggests that the tyrosinase is active in the cell in the form of a monomer. Tyrosinases originating from Streptomyces nigrifaciens , Streptomyces glaucescens , P. putida F6 and B. thuringiensis are all monomers, while Vibrio tyrosinaticus, and T. roseum tyrosinases are dimers [Kong et al, 2000;Liu et al, 2004;McMahon et al, 2007].…”
Section: Purification Of Active His 6 -Tag Tyrosinasementioning
confidence: 99%
See 1 more Smart Citation
“…Influence of temperature: The activity of enzyme was determined by incubating the assay mixture at temperatures ranging from 10 to 100 ᵒC with an increment of 10 ᵒC. The reactions were performed at optimum pH value of the enzyme [24].…”
Section: International Letters Of Natural Sciences Vol 43mentioning
confidence: 99%
“…This enzyme has both monophenolase and diphenolase activity and responsible for the biosynthesis of melanin. It has been produced from various sources such as Escherichia intermedia [6], Bacillus thuringiensis [7], Banana [8], Aspergillus oryzae [9], Portulaca grandiflora [10], Yarrowia lypolytica [11], Acremonium rutilum [12], Brevundimonas sp [13] and Bacillus sp JPJ [1] and Hypericum lariciforium juss [14] Although, it has been observed that very few attempts have been made to produce L-Dopa using bacterial sources. Therefore, the present study is undertaken to isolate and explore L-Dopa producing bacteria present in the soil.…”
mentioning
confidence: 99%